Psychological predictors of short-term lower-limb orthotic device adherence : an exploratory study - Leong, Utek (Nanyang Technological University, 2021)
Although evidence suggests that the effectiveness of lower-limb orthotic device interventions is limited by poor treatment adherence, not much is known about the factors that influence adherence to these devices. We investigated if custom lower-limb orthotic device adherence in the initial 30 days of wear could be predicted by orthotic device satisfaction, the Big Five personality traits, health-related quality of life (HRQoL), illness denial, and body image disturbance measured at baseline. Additionally, we explored if these psychological variables changed after the initial 30 days of wear. We recruited 37 patients who recently received their first ever custom lower-limb orthotic device – 36 foot orthosis users and one ankle-foot orthosis user. Adherence was measured with a daily diary administered for 30 consecutive days. We utilised multilevel logistic regression to assess if any of the proposed psychological factors at measured baseline were predictive of short-term adherence and paired t-tests for the exploratory analyses. After controlling for the daily reported reason for going out, age, and sex, orthotic device satisfaction (z = 3.43, p < .001, OR = 11.45), conscientiousness (z = -2.25, p = .002, OR = 0.19), and openness (z = -2.65, p = .001, OR = 0.08) were independently predictive of adherence. Only body image disturbance [t(35) = -2.20 , p = .035] and the HRQoL domain of energy/fatigue [t(35) = 2.08 , p = .045] significantly changed after 30 days of wear. Our findings here emphasise the need for more concordant patient-clinician relationships to promote orthotic device adherence.